E-Field Probe Integrated with Package Lid - BARNETT RON JAY (2012)
A measurement apparatus is disclosed. The measurement apparatus includes a lid configured to be removably affixed to a microcircuit case. One or more penetrations through the lid allow insertion of a signal-conducting probe. The probe is removably affixed to the lid at the site of the penetration. The probe includes a central conductive pin. The central conductive pin transmits to a connection outside the case a radio-frequency signal inductively received from a source inside the case. The probe also includes a dielectric region radially surrounding a portion of the central conductive pin, and a grounded outer conductive housing radially surrounding the dielectric region and electrically isolated from the central conductive pin by the dielectric region.